Whispers of the Divine: Dreams and their Contested Place in Sunni Islamic Legal Tradition - Hassan, Said (2025)
Islamic law is renowned for its meticulous rules, reliance on material evidence, and detailed procedural standards. Yet, throughout Islamic history, there have been notable cases where dreams and visions, often seen as divinely inspired, have influenced legal decisions. This paper delves into the complex issue of whether and under what circumstances dreams or inspirations can be accepted as legal evidence in Islamic jurisprudence. Through the exploration of classical and contemporary scholarly views, legal texts, and historical precedents, this research aims to provide a nuance understanding of the Sunni Islamic legal perspective on the use of dreams and visions as a basis for legal rulings. The prevailing view in Sunni Islamic jurisprudence largely dismisses dreams as valid legal evidence, interpreting them as symbolic gestures or historical anomalies. However, a minority of scholars advocate for their legal relevance in specific contexts. This study proposes a more refined, intermediate position, suggesting that such experiences may serve as supplementary legal evidence under particular conditions. This study also seeks to analyze the broader theological implications of relying on non-material evidence in a legal system that traditionally values certainty and material proof. While spiritual experiences such as dreams hold great importance in Islamic thought, their place in legal matters remains a topic of debate.